Analisis Faktor Pemanfaatan VCT pada Orang Risiko Tinggi HIV/AIDS - Purwaningsih Purwaningsih; Misutarno Misutarno; Siti Nur Imamah (Jurnal Ners, 2011)
Introduction: Voluntary Counseling and Testing (VCT) is an entry point for the provision of nursing, support and medication of people living with HIV/AIDS. VCT is also a model for the dissemination of comprehensive information and support to change risk behavior and prevent HIV/AIDS infection. The purpose of this research was describe determinants of VCT utilization for the high risk person of HIV/AIDS at Puskesmas Dupak based on health belief model.Method: Design used in this study was descriptive survey design. The population was high risk people of HIV/AIDS who utilize VCT at Puskesmas Dupak Surabaya in 2010. The variables were component of health belief model for the high risk people of HIV/AIDS who utilize VCT. It consist of perceived susceptibility factor, perceived seriousness factor, perceived benefit and barrier factor, self efficacy, and cues to action factor. The samples were recruited with probability sampling consist of 23 respondents. Data were collected by using structured questionnairs with multiple choice questions and were then analyzed using descriptive analysis.Result: Results showed that perceived suscebtibilty was in strong criteria (61%), perceived seriousness was in strong criteria (78%), perceived benefit was in strong criteria (66%), perceived barrier was in enough criteria (65%), self effi cacy was in strong criteria (82%), and cues to action factor was in strong criteria (52%).Conclusion: Component health belief model to VCT utilization on high risk people of HIV/AIDS was in strong criteria. It is recommended to health worker at Puskesmas Dupak to give adequate information frequently to the high risk people of HIV/AIDS.